Systematic review on what works, what does not work and why of implementation of mobile health (mHealth) projects in Africa - Aranda-Jan, Clara B.; Mohutsiwa-Dibe, Neo; Loukanova, Svetla (BMC public health, 2014)
Access to mobile phone technology has rapidly expanded in developing countries. In Africa, mHealth is a relatively new concept and questions arise regarding reliability of the technology used for health outcomes. This review documents strengths, weaknesses, opportunities, and threats (SWOT) of mHealth projects in Africa.